Discharge against medical advice from hospitalizations for substance use disorders: The potential impact of the Affordable Care Act. (1st April 2019) - Zhu, He; Wu, Li-Tzy
Highlights: Discharge against medical advice (DAMA) increases the morbidity or mortality. Time series analysis was conducted to examine the national trend in DAMA. DAMA was common among hospitalizations for substance use disorders. Hospitalizations for opioid use disorder were most likely to have DAMA. The Affordable Care Act was not associated the change in DAMA. Abstract: Objectives: To explore whether the Affordable Care Act (ACA) enactment is associated with changes in the proportion of discharge against medical advice (DAMA) among hospitalizations due to substance use disorders (SUDs). Methods: Data were drawn from the 2012–2015 National Inpatient Samples. The sample comprised hospitalizations with a principal diagnosis of SUD (i.e., SUD-involved hospitalization) for patients aged 18–64 years (unweighted N = 287, 629). Interrupted time series analyses were conducted to evaluate the effect of the ACA on monthly proportions of DAMA among SUD-involved hospitalizations. Results: Overall, approximately 11% of SUD-involved hospitalizations were DAMA. DAMA was most frequently found among hospitalizations for primary opioid use disorder (pre-ACA: 16.4%; post-ACA: 17.2%). Despite the increase in the Medicaid coverage after ACA enactment, there was no significant change in the proportion of DAMA before and after ACA periods across various demographic groups and clinical conditions. Time series analyses also indicated no significant trend effect on the proportion of DAMA during the pre- and post-ACA months. Conclusions: As many as 1 in 10 SUD-involved hospitalizations were considered as DAMA. Concerted efforts are needed to enhance insurance benefits for SUDs and patients' knowledge of SUD treatment benefits in order to increase SUD treatment engagement and completion and to reduce DAMA, especially for substance-using patients with Medicaid or opioid use disorder.